Quantitative trait loci for quality and agronomic traits in two advanced backcross populations in oat (Avena sativa L.). Issue 5 (27th May 2014) - Herrmann, Matthias H.; Yu, Jianzhong; Beuch, Steffen; Weber, Wilhelm E.; Bürstmayr, H.
Abstract Using the advanced backcross quantitative trait loci (AB‐QTL) strategy, we successfully transferred and mapped valuable allelic variants from the high β‐glucan (BG) accession IAH611 (PI 502955), into the genome of cultivar 'Iltis'. By backcrossing one BC1F1 plant to 'Iltis', we developed two BC2F2‐6 populations A and B, comprising 98 and 72 F2‐individuals, respectively. Genotyping of BC2F2 individuals with predominantly AFLP markers resulted in 12 linkage groups with a map size of 455.4 cM for Population A and 11 linkage groups with a map size of 313.5 cM for Population B. Both populations were grown at three sites in Germany over a three‐year period. Individuals were then phenotyped for 13 traits including grain yield (YD) and β‐glucan content (BG). QTL analysis via stepwise regression detected a total of 33 QTLs, most of which were clustered in three linkage groups. Two dense linkage groups A1 and B13 were found to be putatively homologous to groups KO_6 and KO_11 of the 'Kanota'/'Ogle' map, respectively.